2003
DOI: 10.1111/j.1365-2265.2004.01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone replacement in adults and bone mineral density: a systematic review and meta‐analysis

Abstract: There is evidence of a small effect of GH replacement on bone mineral density in adults with GH deficiency. The clinical importance of this is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 31 publications
(30 reference statements)
1
24
1
7
Order By: Relevance
“…Low bone mass has been shown to be less frequent with increasing age in patients with GHD (34). Furthermore, in a meta-analysis, treatment with GH has not been shown to improve BMD in this patient group (35). In our study we found no correlation between BMD or markers of bone turnover and spontaneous growth hormone secretion.…”
Section: Discussioncontrasting
confidence: 52%
“…Low bone mass has been shown to be less frequent with increasing age in patients with GHD (34). Furthermore, in a meta-analysis, treatment with GH has not been shown to improve BMD in this patient group (35). In our study we found no correlation between BMD or markers of bone turnover and spontaneous growth hormone secretion.…”
Section: Discussioncontrasting
confidence: 52%
“…Second, increases in markers of bone remodeling occur during GH replacement therapy in adults with GHD (3,4,8,15). Finally, accumulated evidence supports the finding that GH replacement in children (3,16) and adults with GHD (8,17,18) improves BMD.…”
Section: Introductionsupporting
confidence: 50%
“…Em DGHA, os marcadores bioquímicos de remodelação óssea estão normais ou diminuídos e há diminuição do turnover ósseo (26). A redução de densidade mineral óssea em DGHA é provavelmente resultado de diminuição de formação óssea.…”
Section: Densidade Mineral óSseaunclassified
“…A redução de densidade mineral óssea em DGHA é provavelmente resultado de diminuição de formação óssea. Esta redução é referida em pacientes com DGHA-II e DGH-IA, seja com DGHA isolada ou com deficiência hipofisária múltipla (26).…”
Section: Densidade Mineral óSseaunclassified
See 1 more Smart Citation